The Double-Edged Sword of Grandiose Narcissism - Watts, Ashley L.; Lilienfeld, Scott O.; Smith, Sarah Francis; Miller, Joshua D.; Campbell, W. Keith; Waldman, Irwin D.; Rubenzer, Steven J.; Faschingbauer, Thomas J. (Psychological Science, 2013)
Recent research and theorizing suggest that narcissism may predict both positive and negative leadership behaviors. We tested this hypothesis with data on the 42 U.S. presidents up to and including George W. Bush, using (a) expert-derived narcissism estimates, (b) independent historical surveys of presidential performance, and (c) largely or entirely objective indicators of presidential performance. Grandiose, but not vulnerable, narcissism was associated with superior overall greatness in an aggregate poll; it was also positively associated with public persuasiveness, crisis management, agenda setting, and allied behaviors, and with several objective indicators of performance, such as winning the popular vote and initiating legislation. Nevertheless, grandiose narcissism was also associated with several negative outcomes, including congressional impeachment resolutions and unethical behaviors. We found that presidents exhibit elevated levels of grandiose narcissism compared with the general population, and that presidents’ grandiose narcissism has been rising over time. Our findings suggest that grandiose narcissism may be a double-edged sword in the leadership domain.